The effect and safety of Tai Chi on bone health in postmenopausal women: A meta-analysis and trial sequential analysis - Liu, Xiaobo; Jiang, Chengzhi; Fan, Rong; Liu, Tianyu; Li, Yuxi; Zhong, Dongling; Zhou, Luxiang; Liu, Tao; Li, Juan; Jin, Rongjiang (Frontiers in Aging Neuroscience, 2022)
Background: This meta-analysis and trial sequential analysis aimed to evaluate the effect and safety of Tai Chi on bone health in postmenopausal women. Method: Seven databases were searched from their inceptions to May 11, 2022, to collect randomized controlled trials (RCTs) investigating the effect and safety of Tai Chi on bone health in postmenopausal women. Two independent reviewers identified the eligible studies, extracted data, assessed the risk of bias and rated certainty of evidence. Among included studies, there were 3 comparisons including Tai Chi versus non-intervention, Tai Chi versus other exercise, and Tai Chi plus nutraceutical versus nutraceutical. Subgroup analyses were conducted based on the duration of Tai Chi. Sensitivity analysis and publication bias assessment were performed. We also performed the trial sequential analysis to assess the reliability of the evidence. Results: A total of 25 reports involving 24 studies were included. Four studies were considered as high overall risk of bias, and the rest were some concerns. Compared with non-intervention, Tai Chi was better in improving BMD of lumbar spine, femoral neck, trochanter, but there was no significant difference in increasing BMD of Ward’s triangle. Trial sequential analysis showed that the effect of Tai Chi versus non-intervention on BMD of lumbar spine and femoral neck were reliable, but effect on BMD of trochanter and Ward’s triangle need further verification. Subgroup analysis suggested that Tai Chi training over 6 months had greater improvement in BMD of lumbar spine, femoral neck and trochanter than non-intervention. No significant differences were observed in the above outcomes of Tai Chi versus other exercise, and Tai Chi plus nutraceutical versus nutraceutical. There was insufficient evidence to support the effect of Tai Chi on bone turnover markers and calcaneus quantitative ultrasound. Few adverse events related to Tai Chi occurred. Conclusion: Tai Chi may be an optional and safe exercise for improving BMD loss in postmenopausal women, and Tai Chi practices for more than 6 months may yield greater benefits. However, more rigorously designed RCTs are required to verify the benefits and to explore optimal protocol of Tai Chi exercise for bone health.